2017
DOI: 10.13141/jve.vol8.no3.pp151-155
|View full text |Cite
|
Sign up to set email alerts
|

Application of remote sensing and GIS technique to analyze the land-use change: the case of Phu Giao district, Binh Duong province

Abstract: Digital change detection is a helpful technique using multi-temporal satellite image for analyzing landscape exchange. The objective of this study is an attempt to assess the land-use changes in Phu Giao district, Binh Duong province, Vietnam in the period of fifteen years, from 2001 to 2015. Landsat Thematic Mapper (TM) image data files of years from 2001 to 2015 were collected on website of United States Geological Survey (USGS). Then, the images supervised were classified into five classes including perenni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Specifically, male subjects exhibited a significantly higher prevalence of overweight and obesity (46.9%) than female subjects (21.8%). Comparisons with other studies conducted in different regions show that the prevalence of overweight and obesity among 10-year-old schoolchildren in Hoavang is lower than the rates reported in Hanoi, Vietnam (2021), at 37.8%, 10 and Haiduong, Vietnam (2021), at 27.2%, 5 but higher than rates reported in Bacgiang, Vietnam (2021), at 18.0% 12 ; Nepal (2017) at 25.7% 13 ; Guangzhou, China (2015), at 18.2% 14 ; Uberaba, Brazil (2012-2013), at 32.3% 15 ; and Ivory Coast (2018) at 10.2% 16 . These results raise concerns regarding the alarming rise in childhood obesity within the Hoavang region.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Specifically, male subjects exhibited a significantly higher prevalence of overweight and obesity (46.9%) than female subjects (21.8%). Comparisons with other studies conducted in different regions show that the prevalence of overweight and obesity among 10-year-old schoolchildren in Hoavang is lower than the rates reported in Hanoi, Vietnam (2021), at 37.8%, 10 and Haiduong, Vietnam (2021), at 27.2%, 5 but higher than rates reported in Bacgiang, Vietnam (2021), at 18.0% 12 ; Nepal (2017) at 25.7% 13 ; Guangzhou, China (2015), at 18.2% 14 ; Uberaba, Brazil (2012-2013), at 32.3% 15 ; and Ivory Coast (2018) at 10.2% 16 . These results raise concerns regarding the alarming rise in childhood obesity within the Hoavang region.…”
Section: Discussionmentioning
confidence: 50%
“…2 Recent investigations conducted in Vietnam have unveiled a significant surge in the prevalence of overweight and obesity among school-aged children. [3][4][5] Childhood overweight and obesity carry profound implications for adulthood, with an array of comorbidities encompassing cardiovascular, digestive, renal, endocrine, dermatological, neurological, and orthopedic disorders. As the prevalence of overweight and obesity rises, so does the burden of these associated comorbidities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies in Binh Duong Province reported that vegetation cover change has occurred recently due to the increase in urban areas [13] which causes negative impacts on ecosystems [14][15][16][17]. The study was conducted in Binh Duong Province by Thuy et al showed that some vegetation species are at risk of disappearing due to the reduction of their natural habitat caused by urbanization [17].…”
Section: Introductionmentioning
confidence: 99%
“…Along with Thu Dau Mot, there are some towns developed in the south, such as Lai Thieu, Bung, and Di An. This area had favourable conditions for urbanization and industrialization such as its location near Ho Chi Minh City, convenient rail, and road traffic, a long history of urban development, commercial activities and handicrafts, and dense population (Le 2019). Therefore, after re-establishing the province in 1997, the provincial government focused on urbanization and industrialization in the southern region, including Thu Dau Mot, Thuan An Third, the increasing urbanization rate of the province stems from industrialization.…”
Section: Factors Affecting Urban Expansion From 1995 To 2020mentioning
confidence: 99%